2015
DOI: 10.1111/nhs.12201
|View full text |Cite
|
Sign up to set email alerts
|

A family empowerment program for families having children with thalassemia, Thailand

Abstract: The purpose of this quasi-experimental design study was to examine the effectiveness of a family empowerment program (FEP) on family functioning and empowerment among 56 families having children with thalassemia. The 26 families in the experimental group received the FEP and usual care, while 30 families in the control group received usual care. Data collection occurred through family functioning and empowerment questionnaires. Between-group differences were tested with t-tests and analysis of variance. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…As such, the findings from the studies were presented as a narrative summary under five core themes: illness belief, health literacy, social interaction and communication, social and family support, and spirituality. Full-text articles assessed for eligibility (n= 57) Wacharasin et al 2015 4 Anum & Dasti 2016 14 Efe et al 2012 15 Nabors et al 2013 16 Kermansaravi et al 2018 17 Chusri et al 2019 18 Maheen et al 2015 19 Zaheer et al 2015 20 Habibzadeh et al 2012 21 Gold…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, the findings from the studies were presented as a narrative summary under five core themes: illness belief, health literacy, social interaction and communication, social and family support, and spirituality. Full-text articles assessed for eligibility (n= 57) Wacharasin et al 2015 4 Anum & Dasti 2016 14 Efe et al 2012 15 Nabors et al 2013 16 Kermansaravi et al 2018 17 Chusri et al 2019 18 Maheen et al 2015 19 Zaheer et al 2015 20 Habibzadeh et al 2012 21 Gold…”
Section: Search Resultsmentioning
confidence: 99%
“…The study by Wacharasin et al 4 found that illness belief was a cognitive map guiding the decision when families confront a chronic situation. Illness belief was, therefore, the dominant factor that influenced family functioning and is a crucial factor to understand how families cope with illness and suffering.…”
Section: Illness Beliefmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to fulfil needs results in an imbalance in one's condition that will affect mental and physical health (Asmadi, 2008;Winstanley, Simpson, Tate, & Myles, 2006). The health problems occurred in parents will affect the care of their children with thalassemia and lead an impact on children's health (Mediani et al, 2017;Wacharasin, Phaktoop & Sananreangsak, 2015), besides that, children also spend more time at home with parents compared to hospitals so parents can provide care better for their children (Wilder, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It also helped bring a balance in the family needs and the way they used to meet their needs. 30 The participants in this study were the mothers of children with autistic disorder. Obviously, our findings cannot be generalized to all members of the family.…”
mentioning
confidence: 99%